Growth and Yield Attributes of Gmelina arborea (Roxb.) and Emblica officinalis (Gaertn.) based Agroforestry System on Fallow Lands in Uttarakhand and Uttar Pradesh - Singh, Rambir; Srivastava, Anubha; Singh, Charan; Gulati, Ajay (Indian Forester, 2021)
The present study reflects the growth performance and suitability of Gamhar and Aonla with agriculture crops on fallow lands of farmers in Uttarakhand and Uttar Pradesh states and may be promising for improvement of livelihood at short rotation. Gamhar (Gmelina arborea) and Aonla (Emblica officinalis var. NA-7) both are fast growing species and showed a remarkable performance on fallow lands at Dhaluwala majbata (Haridwar) of Uttarakhand and Fatehpur Pelio (Saharanpur) and Kodapur (Prayagraj) of Uttar Pradesh under agroforestry models established in Randomized Block Design at 4m × 5m and 5m × 5m spacing with rabi crops like Wheat-Barley-Mustard and kharif crops i.e. Groundnut-Til-Millet. On initial observations, soil at Kodapur (Prayagraj) site was alkaline with 8.30 pH in comparison of sites at Dhaluwala majbata (7.12 pH) and Fatehpur Pelio (7.36 pH). Available Phosphorus was in medium ranges at all sites. Available nitrogen and potassium were in low ranges at Dhaluwala majbata in comparison of sites at Fatehpur Pelio and Kodapur. It was also observed that the both species of G. arborea and E. officinalis are performing well on these fallow lands. The growth parameter of G. arborea and E. officinalis showed a regular increase both in height and girth along with agriculture crops at all sites. The Initial Increment of G. arborea with height 1.89 m and girth 18.20 cm in mix;d planting at Dhaluwala with 5×5m spacing and E. officinalis of height 0.75 m in control plot at Fatehpur Pelio with 5×5m spacing and girth 7.11 cm in control plot at Dhaluwala with 4×5m spacing were found maximum in comparison to other sites after one year. After completion of two years, G. arborea and E. officinalis showed max;imum Mean Annual Increment (MAI) in height (4.96m) and girth (44.50cm) respectively in T5 Mi×ed (Gmelina+Agriculture) at 5m×5m of site Dhaluwala majbata and E. officinalis height (2.99m) in T5 mixed at 5m×5m of site Kodapur and Aonla girth (26.10cm) in T1 Aonla control at 4m×5m spacing of site Dhaluwala majbata as compared to other sites. The yield of agriculture crops i.e. Til (1.30 q/ha) and millet (156.0 q/ha) in kharif and wheat (54.5 q/ha) in rabi was observed maximum in T4 (Aonla+Agri) followed by T5 (Mixed+Agri) at 4m×5m at Dhaluwala majbata. Similarly, at site Fatehpur Pelio the yield of groundnut (6.2 q/ha) in kharif and wheat (52.8 q/ha) in rabi was also observed maximum in T4 (Aonla+Agri) followed by T5 (Mixed+Agri) at 5m×5m spacing.